The Role of Teacher Islamic Education in Forming Students’ Moral at State Junior High School 3 Baradatu - Wahyuni, Wahyuni; Jannah, Siti Roudlatul; Fadillah, Kharis (Bulletin of Pedagogical Research, 2022)
The article aimed to find out how the role of Islamic religious education teachers in forming morals of students and the factors that influence the students' moral formation at State Junior High School 3 Baradatu. The method used a descriptive method in a qualitative approach. The data collection used observation, interviews, and documentation. Interviews in this study were conducted on school principals, Islamic religious education teachers and several students. Data analysis in this study used three data analysis techniques, namely data reduction, data presentation and verification or drawing conclusions. While checking the validity of the data using a credibility test which includes: extension of observation, increasing perseverance, triangulation, peer examination, and negative case analysis. towards students. The result showed that through habituation that was carried out through habituation activities such as prayer before lessons begin, reciting the Al Quran starting from 7.00 a.m. - 08.30 a.m. and praying in congregation every day can form the noble character of students at State Junior High School 3 Baradatu. Keywords : Role of Teachers, Forming Morals Values, Students Moral Value